2017
DOI: 10.1186/s12986-017-0228-9
|View full text |Cite|
|
Sign up to set email alerts
|

Antiobesity potential of Piperonal: promising modulation of body composition, lipid profiles and obesogenic marker expression in HFD-induced obese rats

Abstract: BackgroundBlack pepper or Piper nigrum is a well-known spice, rich in a variety of bioactive compounds, and widely used in many cuisines across the world. In the Indian traditional systems of medicine, it is used to treat gastric and respiratory ailments. The purpose of this investigation is to study the antihyperlipidemic and antiobesity effects of piperonal in high-fat diet (HFD)-induced obese rats.MethodsPiperonal, an active constituent of Piper nigrum seeds, was isolated and confirmed by HPLC, 1H and 13C N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 44 publications
4
16
1
Order By: Relevance
“…Therefore, the effects of CSE on abdominal and hepatic adiposity cannot completely be explained by the increase in lipid excretion. TNF-α is an important factor in obesity-related proinflammatory responses and insulin resistance (Meriga et al, 2017;Stanley et al, 2011). In the present study, we found that CSE consumption reduced lipid peroxidation in a dose-dependent manner and ameliorated high-fat diet-induced elevation of hepatic TNF-α and hydroxyproline levels.…”
Section: R a F Tsupporting
confidence: 65%
“…Therefore, the effects of CSE on abdominal and hepatic adiposity cannot completely be explained by the increase in lipid excretion. TNF-α is an important factor in obesity-related proinflammatory responses and insulin resistance (Meriga et al, 2017;Stanley et al, 2011). In the present study, we found that CSE consumption reduced lipid peroxidation in a dose-dependent manner and ameliorated high-fat diet-induced elevation of hepatic TNF-α and hydroxyproline levels.…”
Section: R a F Tsupporting
confidence: 65%
“…The release of free fatty acids is proportional to their levels in coronary sinus. Although these fatty acid molecules are used by the heart in the form of energy sources, excessive deposition of these molecules often leads to triglyceride synthesis that causes hypertriglyceridemia (Balaji et al., 2017; Uddandrao et al., 2019). Lipolysis is also one of the important determinants of ISO‐induced myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the experimental period, rats were fasted overnight and anesthetized with isoflurane and sacrificed. Organs such as liver, Heart, kidney, and Adipose tissues (Mesentric, retroperitoneal, epididymal fat pads) from each rat were surgically removed, after detailed necropsy examination, wet weights were measured with experimental electrical balance (Shimadzu) and stored at - 800C for further studies [32].…”
Section: Methodsmentioning
confidence: 99%